AUDIT SISTEM INFORMASI MENGGUNAKAN METODE FRAMEWORK COBIT 5 - Selamat Soni Harsono Wijaya; RZ Abdul Aziz (IIB Darmajaya, 2019)
Information is one of the most important factors at this time, especially for organizations that use information technology (IT) as a supporter of their business processes. Lampung Post is a company that uses IT to support its business processes. But in its development, technological progress is also used as an opportunity to commit crime in cyberspace or other media that are often known as cyber crime. Cyber crime is to take over the website and also change the contents of the website content that causes harm to the company and also company partners who are still in one group of companies. To maintain the security of corporate information systems, a technology or system with good information security management is needed to safeguard information assets and prevent activities that can harm the company. For this reason, an information system audit is needed to assess current and expected capability of corporate information technology governance. This research on auditing information systems uses the COBIT 5 framework to find solutions to improve corporate information technology governance systems and use a scale of 0-5 in determining the capability level assessment. The results of the information system audit show that the current value is on a scale of 3 (Established), while the value of the excpect is at level 5 (Optimizing).Keywords : Audit, Capability Level, Framework COBIT 5 , Information Systems